2022
DOI: 10.3390/cells11071218
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis: An Acquired Interferonopathy?

Abstract: Myasthenia gravis (MG) is a rare autoimmune disease mediated by antibodies against components of the neuromuscular junction, particularly the acetylcholine receptor (AChR). The thymus plays a primary role in AChR-MG patients. In early-onset AChR-MG and thymoma-associated MG, an interferon type I (IFN-I) signature is clearly detected in the thymus. The origin of this chronic IFN-I expression in the thymus is not yet defined. IFN-I subtypes are normally produced in response to viral infection. However, genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…It has also been shown that oxidative stress and low antioxidant status play a major role in the pathogenesis of inflammatory and autoimmune diseases, and that MG patients with low antioxidant status have active oxidative processes ( Yang et al, 2016 ; Adamczyk-Sowa et al, 2017 ). In addition to this, studies have confirmed that AChR-MG may be an acquired interferon disease ( Payet et al, 2022 ). The results of GO and KEGG analysis in this study also suggest that MG dysregulated genes are mainly enriched in interferon and immune-related processes.…”
Section: Discussionmentioning
confidence: 74%
“…It has also been shown that oxidative stress and low antioxidant status play a major role in the pathogenesis of inflammatory and autoimmune diseases, and that MG patients with low antioxidant status have active oxidative processes ( Yang et al, 2016 ; Adamczyk-Sowa et al, 2017 ). In addition to this, studies have confirmed that AChR-MG may be an acquired interferon disease ( Payet et al, 2022 ). The results of GO and KEGG analysis in this study also suggest that MG dysregulated genes are mainly enriched in interferon and immune-related processes.…”
Section: Discussionmentioning
confidence: 74%
“…Our results showed the target genes STAT1, MCL1, and FOS were upregulated in all cell subsets, and their abundance changed significantly from the normal control and pre-treatment group compared to their levels after treatment, indicating their importance in the remission of MG. STATs are also downstream targets of Janus tyrosine kinases, and the Janus tyrosine kinase/STAT signal transduction pathway mediates a variety of immune-related cytokine signals ( 23 , 24 ). Among these, the type-I interferon (IFN-I) signaling pathway depends on the induction of STAT1 ( 25 ), and IFN-I has been found to increase the risk of MG ( 26 ). Patients with MG exhibit high levels of IFN-I and expression of various IFN-I-induced genes in the thymus ( 27 ), and targeted STAT1 therapy may hold promise for its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The disease has a bimodal incidence pattern, affecting individuals of all ages but with a higher incidence among young women and elderly men. [13][14][15][16] While the pathogenesis of MG remains unclear, [17,18] available therapies for the condition include cholinesterase inhibitors, glucocorticoids, immunosuppressants, intravenous immunoglobulins, plasma exchange, and thymectomy. [19][20][21][22] Emerging treatment options for MG include hematopoietic stem cell transplantation and targeted biologics, such as eculizumab and rituximab, which diversified the available treatment portfolio for MG patients.…”
Section: Introductionmentioning
confidence: 99%